Aware but not prepared: understanding situational awareness during the century flood in Germany in 2021 - Zander, K.K.; Nguyen, D.; Mirbabaie, Milad; Garnett, S.T. (International Journal of Disaster Risk Reduction)
Keywords: Geology; Safety Research; Geotechnical Engineering and Engineering Geology; Building and Construction

The potential of digital nudging to bridge the gap between environmental attitude and behavior in the usage of smart home applications - Stieglitz, Stefan; Mirbabaie, Milad; Deubel, Annika; Braun, Lea-Marie; Kissmer, Tobias (International Journal of Information Management)
Keywords: Library and Information Sciences; Computer Networks and Communications; Information Systems

Digital Nudge Stacking and Backfiring: Understanding Sustainable E-Commerce Purchase Decisions - Mirbabaie, Milad; Marx, Julian; Erle, Lukas (Pacific Asia Journal of the Association for Information Systems)

Analyse von Alterungsmechanismen im Hinblick auf die Effizienz von Haushaltskältegeräten - Paul, Andreas
Die Energieaufnahme von Haushaltskältegeräten ist seit den 1990er Jahren erheblich gesunken. Dieser Wert wird von den Herstellern im Neuzustand der Geräte unter Normbedingungen bestimmt. Wie jedes technische System unterliegen jedoch auch Haushaltskältegeräte einem Alterungsprozess, der zu einem Anstieg der Energieaufnahme über die Zeit führt. Im Rahmen dieser Dissertation wurde auf der Grundlage von 100 Messungen der Energieaufnahme, die an 32 Geräten über einen Zeitraum von 21 Jahren durchgeführt wurden, ein Alterungsmodell entwickelt. Dieses Modell ist das erste, das mit Hilfe von Daten der Energieaufnahme real gealterter Geräte entwickelt wurde. Es beschreibt einen Anstieg der Energieaufnahme von 27 % über die durchschnittliche Einsatzzeit eines Haushaltskältegeräts von 16 Jahren. Der stärkste Anstieg erfolgt in den ersten fünf Betriebsjahren. Durch Diffusionsvorgänge in dem im Gehäuse verbauten Polyurethan-Schaum wird das im Zellgas vorhandene Kohlenstoffdioxid durch Luft ersetzt. Hierdurch steigt die Wärmeleitfähigkeit des Schaums um ca. 33 % an, wodurch sich die Energieaufnahme der Geräte erhöht. Des Weiteren wurde der Einsatz von Paraffinen als Phasenwechselmaterial in Haushaltskältegeräten untersucht. Durch deren Einsatz konnte die Energieaufnahme gesenkt und die Funktionalität der Geräte gesteigert werden. Hierfür sind detaillierte Kenntnisse der Materialkenndaten der Paraffine notwendig. Die Wärmeleitfähigkeit der verschiedenen Paraffin-Stoffgruppen in der festen Phase ist jedoch bisher nur unzureichend untersucht worden. Daher wurde ein Messaufbau entwickelt, mit dem die Wärmeleitfähigkeit von festem Paraffin bestimmt werden kann, und es wurden entsprechende Messungen durchgeführt.

Second grader´s understanding of doubling and halfing in various representations - Schwerin, Imke; Häsel-Weide, Uta (International Symposium in Elementary Mathematics Teaching. Proceedings: New Directions in Elementary Mathematics Education)

Lehre in Zeiten von Digitalisierung und Inklusion - Beispiele aus drei Fächern - Schmidt, Rebekka; Tenberge, Claudia; Häsel-Weide, Uta (Aktive Teilhabe fördern – ICM und Student Engagement in der Hochschullehre)

How to Speak Silently — Rethinking Materiality, Agency, and Communicative Competence in Virtual Reality - A. Erofeeva, Maria; Klowait, Nils; Zababurin, Denis (Sociology of Power)
Keywords: General Medicine

Investigations on the Influences of the Thermomechanical Manufacturing of Aluminium Auxiliary Joining Elements - Borgert, Thomas; Henke, Maximilian; Homberg, Werner (Journal of Manufacturing and Materials Processing)
The demands on joining technology are constantly increasing due to the consistent lightweight construction and the associated increasing material mix. To meet these requirements, the adaptability of the joining processes must be improved to be able to process different material combinations and to react to challenges caused by deviations in the process chain. One example of a highly adaptable process due to the two-step process sequence is thermomechanical joining with Friction Spun Joint Connectors (FSJCs) that can be individually adapted to the joint. In this paper, the potentials of the adaption in the two-stage joining process with aluminium auxiliary joining elements are investigated. To this end, it is first investigated whether a thermomechanical forming process can be used to achieve a uniform and controlled manufacturing regarding the process variable of the temperature as well as the geometry of the FSJC. Based on the successful proof of the high and good repeatability in the FSJC manufacturing, possibilities, and potentials for the targeted influencing of the process and FSJC geometry are shown, based on an extensive variation of the process input variables (delivery condition and thus mechanical properties of the raw parts as well as the process parameters of rotational speed and feed rate). Here it can be shown that above all, the feed rate of the final forming process has the strongest influence on the process and thus also offers the strongest possibilities for influencing it.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Friction-Induced Recycled Aluminium Semi-finished Products in Thermo-mechanical Joining Technology - Borgert, Thomas; Homberg, Werner (Lecture Notes in Mechanical Engineering)
Due to current global challenges regarding energy security as well as climate change the importance of preserving the nature and all available resources is steadily increasing. In order to achieve the energy-saving and climate targets, it is not only necessary to develop new processes and processing possibilities, but also to optimise known process chains with regard to energy and resource efficiency in the area of production technology. Here, the recycling of supposed production waste represents an opportunity to save energy. In addition to the conventional and smelting metallurgical recycling process, extensive research activities have therefore been carried out for alternative solid-state recycling processes. One example is the friction-induced recycling process, which has been used in past studies to demonstrate the energy- and resource-efficient production of semi-finished products from aluminium scrap such as chips. In addition, properties like chemical composition and strength can be adjusted locally and in terms of processing time. This can be used to improve the versatility of further processing steps.

Mit dem Leben Schritt halten - Eine Analyse des Wearable-Dispositivs - Schloots, Franziska Margarete
„Lerne deinen Körper besser kennen“, „Das Beste für deine Gesundheit“ und „Ihre Transformation beginnt jetzt“ - mit Versprechen wie diesen vermitteln die Produkttexte von Wearables wie Fitnesstracker und Smartwatches ein ganz bestimmtes Bild ihrer vorgesehenen Nutzer*innen und deren Nutzung. Verbunden mit den kleinen, am Handgelenk getragenen Geräten sind Fragen nach Erkenntnisgewinn und Kontrollverlust, Selbstoptimierung und Quantifizierungslogiken, Eigenverantwortung und Fremdsteuerung. Die vorliegende Arbeit widmet sich diesem komplexen Spannungsfeld und verfolgt dabei einen multiperspektivischen Ansatz: im Rahmen einer Dispositivanalyse werden die einzelnen Elemente des Wearable-Dispositivs als eigenständige, empirisch zu untersuchende Analysegegenstände betrachtet, um so das Zusammenwirken und die komplexe Beziehung von Diskursen, Gegenständen, Nutzung, Subjekten und Gesellschaft zu erforschen. Ein besonderes Erkenntnisinteresse liegt dabei auf dem Wissen, was sich über Wearables etabliert hat und sich in den Alltagspraktiken der Nutzer*innen widerspiegelt sowie bei der Frage nach den möglichen Funktionen und Auswirkungen des Wearable-Dispositivs.
Keywords: Selbstvermessung; Dispositivanalyse; Gesundheitsdiskurs; Quantifizierungsgesellschaft; Wearables; Selbstoptimierung

Mesh- and model adaptivity for elasto-plastic mean-field and full-field homogenization based on downwind and upwind approximations - Tchomgue Simeu, Arnold; Mahnken, Rolf (XI International Conference on Adaptive Modeling and Simulation)

Digital technology usage as a driver of servitization paths in manufacturing industries - Harrmann, Lisa Katharina; Eggert, Andreas; Böhm, Eva (European Journal of Marketing)
Purpose This study aims to conceptually propose and empirically validate a path perspective on the servitization process of manufacturing firms. It identifies a customer and an outcome path to servitization, sheds light on the pivotal role of digital technology usage for both value-creating paths and explores their financial and relational performance outcomes. Design/methodology/approach The authors use a mixed-method approach, combining a qualitative study with a cross-sectional survey in the USA, the UK and Germany. Findings Manufacturing firms choose between two generic paths to servitization, a customer and an outcome path. Digital technology usage is equally important for both value-creating paths. Progress on the outcome path has a positive effect on firms’ financial performance, whereas the customer path has an indirect effect only, fully mediated by firms’ relational performance. Customer tenure and customer’s open-mindedness are contingency variables in the digital technology usage – servitization path – firm performance framework. Research limitations/implications A path perspective is useful to conceptualize the servitization processes in manufacturing industries. Future research should investigate the sequential choice of servitization paths and explore its drivers and performance outcomes. Practical implications To create and claim superior value for their customers, managers can choose between two servitization paths, leading to differential performance outcomes. While digital technology usage is key to progress on both paths, it is particularly effective for newly acquired customers on the customer path. Suppliers should target their value-creating service offerings at open-minded customer firms to reap their full performance potential. Originality/value Propose and empirically validate a path-perspective on servitization. Understand the pivotal importance of digital technology usage for both servitization paths.
Keywords: Marketing

Der Hauptschulabschluss als sozial selektiver Hauptzulieferer des Übergangssystems - Sommer, Christian (Berufsbildung. Zeitschrift für Theorie-Praxis-Dialog)
Über zwei Drittel der Anfänger*innen im Übergangssystem verfügen maximal über einen Hauptschul-/Mittelschulabschluss. Sie sind damit überrepräsentiert, was sich weniger durch ihre Kompetenzen als mit ihrem sozioökonomischen Status und klassenspezifischen Nachqualifizierungsverhalten erklären lässt.
Keywords: Social inequality; Transition system

»In der Art von Inschriften«. Emblematische Inschriftendichtung als Darstellungsprinzip von Ferdinand von Fürstenbergs Monumenta Paderbornensia (1669 und 1672) - Süßmann, Johannes (Monumenta. Erinnerungsorte zwischen Weser und Lippe. Die Monumenta Paderbornensia des Ferdinand von Fürstenberg)

Perceptions of inclusion in students with diagnosed behavioural, emotional and social difficulties (BESD) displaying internalising and externalising behaviour in inclusive and special education - Zdoupas, Philippos; Laubenstein, Désirée (European Journal of Special Needs Education (Latest Articles))

Entwicklungszielgespräche in der Sekundarstufe I - Systemisches Coaching mit Schüler:innen nach dem GROW-Modell - Zdoupas, Philippos; Lara, Kuhlhoff; Martin, Grust; Jaekel, Anne-Marie; Jan, Ehlert

Predicting the development of digital media PCK/TPACK: The role of PCK, motivation to use digital media, interest in and previous experience with digital media - Schubatzky, Thomas; Burde, Jan-Philipp; Große-Heilmann, Rike; Haagen-Schützenhöfer, Claudia; Riese, Josef; Weiler, David (Computers & Education)
Keywords: Education; General Computer Science

ElectricGrid.jl - A Julia-based modeling and simulationtool for power electronics-driven electric energy grids - Wallscheid, Oliver; Peitz, Sebastian; Stenner, Jan; Weber, Daniel; Boshoff, Septimus; Meyer, Marvin; Chidananda, Vikas; Schweins, Oliver (Journal of Open Source Software)
Keywords: General Earth and Planetary Sciences; General Environmental Science

Scholarship of Teaching and Learning (SoTL) als Motor für eine inter- und transdisziplinäre Hochschuldidaktik - Arnold, Maik; Vöing, Nerea; Reisas, Sabine (Hochschulbildung: Lehre und Forschung)
SoTL ist eine forschungsbasierte Haltung, die die Hochschullehre verbessern und innovieren will. Das deutschsprachige SoTL-Netzwerk hat fünf Thesen formuliert, die SoTL als Grundhaltung und Motor für Lehrentwicklung betonen. Der Beitrag diskutiert diese Thesen und stellt Aktivitäten des Netzwerks vor, die SoTL an Hochschulen und Universitäten fördern und vernetzen wollen. Dabei wird auch die Rolle der »Teacher-Researcher« hervorgehoben.

Structural transitions during Ni nanoparticle formation by decomposition of a Ni-containing metal-organic framework using in-situ total scattering - Prinz, Nils; Strübbe, Sven; Bauer, Matthias; Zobel, Mirijam (New Journal of Chemistry)
For improved and rational design of catalysts, in-depth knowledge of their formation and structural evolution during synthesis is a key parameter. Thus, preparation of a Ni methanation catalyst derived from...
Keywords: Materials Chemistry; General Chemistry; Catalysis